The First Film Narratology—without Films (KULT_online, 2011)
Markus Kuhn designs a highly complex film narratology on the basis of a very good research and summary of the narratological research done so far in Literature and Film Studies. Genette's narratological terms and definitions are translated into the film studies without ignoring the different mediality of the film. The progression of Kuhn's theory can be difficult to follow, as examples are only very briefly explicated.